'Ac si ignis elementaris ibi arderet': Richard Rolle's Elemental Love. (29th October 2020) - Abbott, Jean
Abstract: The 'sensuous' imagery of Richard Rolle's Incendium Amoris is typically regarded as spiritual metaphor—albeit a very material-seeming one. However, the trio of spiritual sensations Rolle explores at length in this work ( fervor, dulcor, and canor ) has a more precise, systematic connection with the physical world via the theory of the four terrestrial elements—a cornerstone of medieval natural philosophy. Through his imagery and descriptions, as well as his own reported actions and reactions, Rolle sets up the burning of fervor as a spiritual mirror of physical fire, the breath of canor as air, and the flowing sweetness of dulcor as water. The fourth member of this elemental system, representing earth, is the human soul that experiences one or more of the other elements of God's love. The resemblance between these spiritual and physical elements is so pervasive, and Incendium exploits it so effectively, that Rolle must carefully and repeatedly specify that they are not, in fact, the same thing. Describing the ineffable through these concrete natural phenomena offers a useful framework for understanding a complex spiritual concept; however, through the idea that elements can transform into one another, it also offers a way of conceptualizing how the devout soul may be fully enveloped in God's elemental love.